TATA KELOLA RUANG KELAS SEBAGAI PENUNJANG EFEKTIVITAS PEMBELAJARAN DI SEKOLAH DASAR - Chichi Elsa Nurhayati; Dina Ramdini; Mira Nurazijah; Nisa Ageng Hayati; Saskia Nurbayanti; Prihantini (STKIP Subang, 2025)
Classroom governance not only serves to maintain order but also plays a direct role in increasing the effectiveness of the learning process. This article aims to outline the principles, components, and relationship between classroom governance and learning effectiveness, as well as the role of teachers in classroom governance. This study employed a literature review method, employing data analysis techniques through several stages, including collecting, reducing, and drawing conclusions from various sources. The analysis revealed a strong relationship between classroom governance and learning effectiveness in elementary schools. Well-managed classrooms have been shown to improve student concentration, motivation, and engagement in learning. Therefore, optimal classroom governance supports not only cognitive aspects but also students' social and emotional development, while facilitating teachers' effective role.